Ethical Governance in the Age of Artificial Intelligence: Challenges and Opportunities for the Balkans - Marsili, M. (The Annals of the University of Oradea, International Relations and European Studies series, 2026)
This paper examines the ethical and political implications of Artificial Intelligence (AI) in governance, with a focus on the Western Balkans in the broader context of European integration and democratic transformation. AI technologies increasingly shape decision-making, policy implementation, and public discourse, offering opportunities for efficiency, transparency, and citizen participation. Yet they also raise significant risks of surveillance, algorithmic bias, and reduced accountability, particularly in regions facing fragile democratic institutions, ethnic diversity, and complex security challenges. Drawing on political philosophy, ethical theory, and contemporary debates in digital governance, this study develops a normative framework for ethical AI adoption grounded in democratic values and human rights. Empirical references to governance practices in the Western Balkans, alongside comparative insights from Central and Eastern Europe, highlight both regional vulnerabilities and potential pathways for responsible AI integration. The paper argues for cross-border cooperation, civil society involvement, and policy harmonization with EU standards as essential conditions for building ethical AI governance. By addressing both risks and opportunities, it contributes to debates on democratization, security management, and the role of emerging technologies in shaping the future of governance.